Handbook of probiotics and prebiotics - Yuan Kun Lee; Salminen Seppo (Canada A John Wiley &Sons, 2009)
Since the publication of the first edition in 1999, the science of probiotics and prebiotics has matured greatly and garnered more interest. The first handbook on the market, Handbook of Probiotics and Prebiotics: Second Edition updates the data in its predecessor, and it also includes material topics not previously discussed in the first edition, including methods protocols, cell line and animal models, and coverage of prebiotics. The editors supplement their expertise by bringing in international experts to contribute chapters. This second edition brings together the information needed for the successful development of a pro- or prebiotic product from laboratory to market.
Keywords: Food Science